ANALYZING COMMUNICATIVE GESTURE OF ENGLISH EDUCATION DEPARTMENT STUDENTS IN PRESENTING RESEARCH PROPOSAL AT UIN ALAUDDIN MAKASSAR - Indah Miftah Awaliah; Arsita Andini Arfan; Sitti Nurpahmi (ETERNAL (English, Teaching, Learning and Research Journal), 2022)
This study discusses the problem of signs, commonly known as eye contact, adapting to head-grabbing and head-rubbing movements, and affecting the expression of a person's facial expressions. Which action is more commonly used during a presentation workshop proposal, and what other factors besides nervousness can affect concentration during a presentation workshop? This study aimed to determine the types of movements students use during seminar presentations and to identify other factors that may affect students' concentration during seminar presentations. The research design employed in this study was mixed methods and the study involved 15 respondents who gave a seminar examination to the proposal. Field notes, videos, questionnaires and interviews were used as data collection tools. Data collection was done by recording respondents as they took seminar exams and then recording the most important parts in field notes, after which researchers distributed questionnaires to the respondents to be studied and interviewed them to find more data. The researchers carried out four activities: observing the research process until data presentation, filling out questionnaires, analyzing and describing the obtained data. Findings from this study suggest that the gestures that students use more frequently when making seminar presentations are sign gestures, or better known as eye contact gestures. When taking a seminar exam, besides nervousness, there are several factors that can affect a student's concentration, the first being the environment, anxiety, depression, and finally overthinking.